Prática mental funcional orientada a tarefa da marcha de amputados de membro inferior - Rodrigo Gontijo Cunha (2015)
Background: Mental Practice (MP) is a cognitive strategy based on motor imagery that may influence the acquisition of motor skills and functional performance. Objective: To analyze the influence of gait-oriented mental practice (MP) in the process of rehabilitation for transtibial amputees, by analyzing the antero-posterior (AP), vertical (V) and medio-lateral (ML) forces and duration of support phase and speed. Methods: The experimental design included evaluation in four distinct moments: Baseline; Pre-MP; Post-MP and Follow-up. Volunteers were divided in 2 Groups: Group A, consisting of 10 volunteers performing the imagination of motor tasks related to the gaits kinematic components; and Group B, consisting of 5 volunteers performing the imagination of a non-motor task. MP sessions were performed from a first-person perspective for 40 minutes, 3 times per week, over 4 weeks. The kinetic analysis was performed based upon the temporal series of the ground reaction force. Results: In Group A, all variables were statistically different (p 0.002) between Pre-MP and Post-MP assessment. The vertical force V1 peak showed decreased, while V2 increased. The antero-posterior force (AP1 peak) was minor, while the AP2 was greater. The medio-lateral showed a significant decrease. The duration of the support phase and speed, showed a significant increase and decrease, respectively. The results obtained at Post-MP assessment were maintained in Follow-up. In Group B, such changes did not occur and there were not found significant differences between the 4 evaluations (Baseline, Pre-MP, Post-MP and Follow-up). Conclusions: Functional task-oriented MP in the rehabilitation process of transtibial amputees altered the kinetic variables and hence improved gait performance. Therefore, it becomes a useful intervention for the rehabilitation of the gait of transtibial amputees.